The Role of Social Partnership in the Regulation of Social and Labor Relations in Ukraine - Buntovskaya, L.L. (Економічний вісник Донбасу, 2013)
With the transition to market economic conditions the problem of enhancing the role of social partnership as a main method of achieving the compromise in conflict-free regulation of social and labor relations has become especially actual. The paper focuses on such main forms of realization of social partnership as social dialogue, collective bargaining, branch, regional agreements and General agreement. It is marked that Ukraine has done a lot in this area. The law of Ukraine “On Social Dialogue” was adopted, the steps are taken to adapt the national legislation on social partnership to the international standards, some ILO Conventions and Recommendations that relate to collective bargaining were ratified. However, there are many problems which are not solved yet. According to the purpose of this study, the present situation with social partnership relations in Ukraine has been analyzed, and the drawbacks have been revealed which significantly increase the potential for conflicts at the production level, in particular numerous violations of the collective agreements’ terms by employers, the low coverage of employees by collective agreements, the formalism in their preparation or failure to enter into them, etc. The grounds are given why it is necessary to increase the responsibility of stakeholders for elaboration and implementation of collective agreements on the legislative level, as well as for the resistance of employers to conclude them. The arguments are advanced to pay attention to the importance of inclusion of provisions on promotion of production democracy into collective agreements, branch and regional agreements. It will help to eliminate the causes of protest moods in working collectives. The importance of creating the effective mechanism of social partnership with business is stressed, and the conclusion is made that to solve this task it is necessary to accelerate the elaboration and adoption of the Law of Ukraine “On Social Responsibility of Business”. It is emphasized that the organization of the system of teaching conflict resolution on the permanent basis is of great importance, as well as the training of qualified specialists in the field of settlement of labor disputes (conflicts). У статті досліджено проблему забезпечення стабільності соціально-трудових відносин в Україні шляхом використання механізмів соціального партнерства та соціального діалогу. Надано пропозиції щодо підвищення ефективності соціально-партнерської взаємодії між суб’єктами господарювання. Обґрунтовано необхідність організації на постійній основі системи підготовки кваліфікованих спеціалістів у сфері врегулювання трудових спорів (конфліктів). В статье исследована проблема обеспечения стабильности социально-трудовых отношений в Украине путем использования механизмов социального партнерства и социального диалога. Даны предложения по повышению эффективности социально-партнерского взаимодействия между субъектами хозяйствования. Обоснована необходимость организации на постоянной основе системыподготовки квалифицированных специалистов в сфере урегулирования трудовых споров (конфликтов).